Plumbago Zeylanica Roots: A Potential Source For Improvement of Learning and Memory - VINEET MITTAL; SHARMA S. K.; PAWAN JALWAL; ANIL HOODA; J.MOR (International Journal of Pharma and Bio Sciences, 2010)
The present study is to investigate the effect of Plumbago zeylanica roots on learning and memory of mice. The exteroceptive behaviour model (Elevated plus maze and Passive avoidance paradigm) and interoceptive behaviour model i.e. scopolamine induced amnesia were employed to evaluate the effect of Plumbago zeylanica roots on learning and memory of mice. The Chloroform extract of Plumbago zeylanica ( 100, 200 and 400 mg/kg. p.o.) was administered for 10 successive days in separate group of animals. The Plumbago zeylanica at dose 200mg/kg. has shown promising memory enhancing effect in mice. Furthermore, the extract significantly reversed the amnesia induced by scopolamine (0.4mg/kg i.p.). The reversal of scopolamine induced amnesia may be due to facilitation of cholinergic transmission in mice brain. Antioxidant, hypolipidaemic and anti-atherosclerotic properties of P. zeylanica may be contributing favourably to memory enhancing effect.